Antimicrobial sulphonamide azo dyes. (23rd October 2019) - Gaffer, Hatem E.
Abstract: Sulphonamide motifs are widely found in many drug candidates with relevant biological activity. Moreover, sulphonamide azo dyes are interesting candidates for synthetic chemists because such dyes provide access to a broad range of functional group transformations. Therefore, many synthetic procedures for the preparation of sulphonamide azo dyes have been developed in recent decades, and the search for rapid and efficient protocols is ongoing. The current article aims to review recent trends in the synthesis of sulphonamide azo dyes and their applications as high‐performance colorants with antimicrobial activity. For convenience, the diverse uses of sulphonamide azo dyes are discussed from the perspective of the application type rather than the structural class.